Higher Education Financing in Ghana: The Case of Ghana Education Trust Fund (GETFund) (Higher Education Politics and Economics, 2026)
I examine the Ghana Education Trust Fund (GETFund), an agency established by the Ghanaian government to finance higher education institutions.  I focus on the organizational and governance structure of the GETFund and the autonomy of the GETFund. Some important research questions in the literature include the justification for creating such funds, the extent of power these funds hold, and the degree of control sector ministries exert over them. If the autonomy and control issues are addressed properly by giving the GETFund a more appropriate level of autonomy, the Fund can use its resources to the fullest. Still, as it stands, it appears that the GETFund does not have its statutory autonomy, leading to a clash of goals. This limited autonomy of the GETFund does not help the management of the fund understand the complexity of the revenue streams and their effect on the GETFund’s organizational and governance structure.